A Design Thinking Techniques Recommendation Tool: An Initial and On-going Proposal - Parizi, Rafael; Moreira, Marina; Couto, Igor; Marczak, Sabrina; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2020: Anais do XIX Simpósio Brasileiro de Qualidade de Software, 2020)
Putting the user at the center of the process has been considered key to achieve quality in modern software development. Discovering and framing the user needs are necessary activities to produce better quality software that fits the customer's needs and their satisfaction. User-centered Design approaches such as Design Thinking (DT) help to establish a creative mindset through convergent and divergent working spaces that allow for the team to better understand, to create empathy, to brainstorm ideas, to prototype, and to test innovative solutions in software development. However, navigating in this world is still challenging. Literature reports on the use of a large spam of techniques to support DT. Selecting an appropriate set of techniques considering the project context, the stakeholders’ profiles, and other characteristics may be challenging, mainly to novice professionals. Thus, as part of an on-going long-term research project, we propose Helius, a collaborative recommender system for DT techniques in software development. Helius provides features supporting recommendations of DT Techniques based on the user previous experiences, techniques’ evaluation ratings, and community feedback. This paper focuses on our preliminary results upon the tool proposal–on a comparison of Helius features with other related tools using the DESMET method. This comparison shows that Helius brings new features for the recommendation of DT techniques, thus, contributing to process quality improvement.